Corrosion and tribological behaviour of electroless Ni–P/nano-SiC composite coating on aluminium 6061. (September 2015) - Soleimani, R.; Mahboubi, F.; Kazemi, M.; Arman, S. Y.
<x content-type="archive" xml:space="preserve">Abstract</x> Ni–P/nano-SiC composite coating was successfully deposited on 6061 aluminium alloy by electroless coating process. Scanning electron microscopy equipped with energy dispersive spectroscopy as well as Vickers hardness tester was utilised to examine the effect of nano-SiC particle incorporation on the morphological and hardness properties. Pin on disc method was applied to investigate the tribological properties of the coatings. Moreover, the corrosion behaviour of coatings for the protection of 6061 aluminium alloy in 3·5 wt-%NaCl solutions was studied using potentiodynamic polarisation and electrochemical impedance spectroscopy. Results showed that incorporation of silicon carbide nanoparticles in the coatings enhances the corrosion and tribological properties of the composite coatings.